Proof through the night : music and the great war - Watkins, Glenn, 1927- (University of California Press, 2003)
Watkins's narrative argues that 20th-century Modernism was not launched full force with the advent of the Great War but rather was challenged by a new set of alternatives to the prewar avant-garde.